Analysing K-Beauty Brands from the Consumer–Brand Relationship Perspective - Sulhaini Sulhaini; Rusdan Rusdan; Sulaimiah Sulaimiah; Rahman Dayani (Universitas Prasetiya Mulya, 2022)
This study examines relationships between foreign brand halo effect and beauty consciousness on self-brand connection in beauty consumption. It also investigates the moderating role of age on these relationships. Data is gathered through an online survey focusing on two South Korean beauty (K-beauty) brands. The results contribute to consumer–brand relationships and international marketing literatures. There is no difference between young adult female and mature adult female consumers in the influence of beauty consciousness on self-brand connection. However, there are substantial differences between the two groups of consumers in the influence of the foreign brand halo effect on self-brand connection. Also, the halo effect exhibits the greatest influence on willingness to pay more. Consumers are also willing to pay more for brands from countries that have a positive image. https://doi.org/10.21632/irjbs.15.1.39-52